KELUARGA DISULFIT PROTEIN ISOMERASE ANGGOTA 4(PDIA4) DI KANKER PAYUDARA DENGAN METASTASIS - Stefanus Lembar; Sheella R. Bororing; Lilis Lilis (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Protein disulfide isomerase (PDI) is a member of thioredoxin superfamily that is secreted in the lumen of the endoplasmic reticulum (ER) in mammalian cells. PDI catalyzes disulfide bond formation, reduction, or isomerization of newly synthesized proteins in the lumen of the RE. PDIA4 is a member of the PDI family, which is also expressed in the mammary gland. Low expression of PDIA4 probably as a result of the stress of RE in hypoxic conditions. These conditions will enhance the ability of tumor cells in mammary tissue to divide aggressively and metastasize. A total of 61 breast cancer patients aged 23−90 years (60 women and 1 man) in Jakarta, Indonesia have participated in this study after signing the informed consent letter. The diagnosis of metastasis is confirmed by the examination of bone scanning. Measurement of PDIA4 concentration is performed by the quantitative enzyme-linked immunosorbent assay (ELISA) using a commercial kits. Based on the examination of the bone scanning, there were 23 (62.5%) subjects with metastatic and 38 (37.5%) subjects non-metastatic. The mean of age of the subjects with metastatic were significantly higher than non-metastatic subjects (p=0.028), which is 51.4 (45.9–56.8) and 44.2 (40.4–48.0). The median of PDIA4 concentrations in serum of subjects with metastatic, i.e. 7.7 (1.0–37.2) ng/ml was significantly lower than non-metastatic subjects (p=0.044), i.e. 9.4 (2.2–69. 6) ng/mL. The concentration of PDIA4 in serum of breast cancer patients with metastatic were significantly lower than non-metastatic patients. It shows that the concentration of PDIA4 have decreased in incidence of metastatic breast cancer.